Tempos de aplicação de um primer autocondicionante: efeitos na adesão e no comportamento à fadiga de uma cerâmica de dissilicato de lítio - Dapieve, Kiara Serafini (2020)
This dissertation is composed of two studies. Study 1 aimed to evaluate the effect of different etching times of the ceramic primer (E&P, Monobond Etch & Prime) on the durability of the microshear bond strength (μSBS) between a lithium disilicate ceramic and a resin cement. The ceramic samples were subjected to an in-lab simulation of Computer-aided design/Computer-aided manufacturing (CAD/CAM) milling and randomly allocated considering: “surface treatment” - 5% hydrofluoric acid and silane (HF5 + SIL) or E&P (20s+40s; 20s+2min; 20s+5min; 20s+10min); and “aging condition”: short-term (tested 24 h after bonding) or long-term (stored for 180 days + 12,000 thermal cycles). Thereby, resin cement cylinders were built, submitted to the μSBS test and the failure pattern was determined. In the short-term, all groups presented statistically similar bond strength (22.42 – 25.06 MPa). However, only the E&P20s+40s (19.25 MPa) and E&P20s+5min (21.51 MPa) groups maintained a stable long-term bond strength, in which the latter was statistically higher than HF5+SIL (17.05 MPa). Most failures were predominantly adhesive. Thus, the use of ceramic primer is a viable alternative to conditioning with 5% hydrofluoric acid and silane, providing a stable bond strength for passive application of 40 s or 5 min. Study 2 aimed to evaluate the effect of increased time of passive application of ceramic primer on the fatigue performance of adhesively cemented lithium disilicate simplified restorations. Ceramic discs (Ø= 10mm; thickness= 1.0mm) were submitted to the same CAD/CAM simulation process and allocated according to: “surface treatment” - PRIMER, coupling agent application only; HF5 + PRIMER, 5% hydrofluoric acid and coupling agent; E&P20s+40s and E&P20s+5min, etching with E&P for 20 s of active application followed by 40 s or 5 min of passive application, respectively; and “aging condition” - baseline, tests performed after 24 h within 5 days of cementation; or aged, storage for 90 days of storage + 12,000 thermal cycles. The adhesive cementation was performed onto epoxy resin discs (Ø= 10 mm; thickness= 2 mm) and the cemented assemblies were submitted to the fatigue test by step-stress approach (initial load of 200 N; step-size of 50 N for each 10,000 cycles; 20 Hz). In the baseline condition, the surface treatments presented similar fatigue performance, except for E&P20s+5min group (940.0 N; 123,000), which presented higher value than PRIMER (786.7 N; 92,333). When aged, the PRIMER group had worst fatigue performance (480.8 N; 31,154) compared to the other groups (810.0 – 840.0 N; 97,000 – 103,000 cycles). In addition, treatment with PRIMER showed unstable fatigue performance after aging. Thus, etching the ceramic surface is required for stable fatigue performance of adhesively cemented lithium disilicate restorations. In addition, the E&P ceramic primer promoted similar fatigue performance compared to the treatment with 5% hydrofluoric acid and coupling agent, but the passive increase in etching time did not improve the fatigue behavior.